Opisane, przypomniane - Wycykał, Monika (Śląskie Studia Polonistyczne, 2013)
The review discusses the latest book by Sławomir Buryła entitled Tematy (nie)opisane. Three essays in which the author deals with the issues that are absent or misrepresented in literary studies devoted to the Holocaust constitute the very article. Buryła makes a difficult attempt to consider how the Polish literature comes to terms with painful topics such as looting, informing, and a moral evaluation of Hitlerites. Making use of a rich written material, the author shows how many areas are still under-read despite a peculiar “overproduction” of texts on Shoah. Books commented on by Buryła allowed him to show numerous tensions, worries and the lack of homogeneity when going through one of the most traumatic experiences in the history of mankind. The book seems to be even more important because it inscribes itself into the trend of the current social and political life where it is more and more difficult to experience the basic value of the humanities such as understanding other people and their suffering.